Moderating Role of Activa Structure on Bond Prices of Manufacturing Companies on the Indonesia Stock Exchange - Tarigan, Rio Adrianus; Sihotang, Ronny Buha; Sitompul, Grace Orlyn (International Journal of Business, Law, and Education, 2024)
The aim of this research is to explore and quantify the interplay among interest rates, inflation, and market risk factors concerning bond prices, with asset structure playing a moderating role. Employing an associative quantitative approach, the study focused on 32 companies that issued bonds on the IDX between 2019 and 2021. A saturated sample technique (Census) was utilized, encompassing all 128 data points (n) from the population. Data analysis employed Moderating Regression Analysis (MRA). The findings indicate that interest rates and inflation individually exert a significant influence on corporate bond prices on the IDX. However, market risk does not demonstrate a significant impact on bond prices individually. Nevertheless, collectively, interest rates, inflation, and market risk jointly affect bond prices. The moderation test results, including the residual test, reveal that asset structure does not moderate the relationship between interest rates, inflation, and market risk on bond prices.